Pengembangan Lembar Diskusi Siswa (LKS) Berbasis Sintaks Quantum Learning Terintegrasi Aplikasi Quisiss Pada Materi Kesetimbangan Benda Tegar - Ikhsan, Imaddudin; Sugianto, Sugianto (UPEJ Unnes Physics Education Journal, 2021)
This study aims to develop a student discussion sheet based on quantum learning syntax and integrated with the quizizz application that can be used as an assistive medium in learning physics about rotational dynamics and rigid object equilibrium. The data taken from this study were in the form of feasibility validation test data and response questionnaires from high school physics teachers and physics education students. This research is a Research and Development (R&D) research which uses a 3D procedure (Define, Design, Develop) which is taken from the 4D model (Define, Design, Develop, Disseminate) by Thiagarajan. The data obtained were analyzed using quantitative descriptive method and the results of the content validation test were 84.5% in the feasible category, 93.75% presentation feasibility in the very feasible category, 96.87% media feasibility in the very feasible category. feasible category, language feasibility 83.30% in the feasible category, and the average in all categories 89.60% in the very feasible category, it can be concluded that LDS can be used in an outline to increase student understanding. The response data for high school physics teachers is 81.12%, including in the positive response category, and 88.11% student responses in the very positive category, this shows that teacher and student assessments developed by teachers and students are good products and can be used in study.